Meaning in life as a protective factor against depression - Baquero-Tomás, Marina; Grau, Mª Dolores; Moliner, Adoración-Reyes; Sanchis-Sanchis, Alejandro (Frontiers in Psychology, 2023)
The main objective of this study was to analyse the mediating role that meaning in life has between emotion dysregulation and depressive symptomatology in Spanish university students.Five hundred and sixty-six Spanish university students participated in the study. All of them completed the Difficulties in Emotion Regulation Scale (DERS), the Patient Health Questionnaire (PHQ-9) and the Purpose in Life Test (PIL-10). A mediation model was performed to test the hypothesis that meaning in life mediates the effect of emotional dysregulation on depressive symptomatology in college students. The results show a positive, moderate, and statistically significant correlation between depression and emotional dysregulation. In addition, a negative, moderate, and statistically significant correlation was found between depression and meaning in life, and a negative, small, and statistically significant correlation between emotional dysregulation and meaning in life. Finally, the results of the mediation model evidence the role of meaning in life in different emotional dysregulation strategies and depressive symptomatology. These findings suggest the importance of incorporating the meaning in life variable in the development and implementation of prevention and treatment programs for psychological disorders.